2022
DOI: 10.3389/fphy.2022.950929
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding the Electron Transport Through Metal-Azurin-Metal Junctions

Abstract: Azurin proteins are the workhorse of protein electronics. This is a branch of biomolecular electronics, a recent research field which investigates electronics based on biomolecules such as proteins, peptides, amino acids, bacterial nanowires or DNA. In general, the possibility of including biosystems in solid-state junctions has opened the way to the development of novel electrical devices, and proteins have attracted enormous attention thanks to their many interesting properties. In the particular case of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…26 For instance, regarding the electron transport mechanism through azurin-based junctions, there is still a debate over the mechanism of electron transport through azurin-based junctions, including the types of transport mechanism (coherent vs. incoherent) and the role of the metal ion that takes place in the system. 23,121 Experimental studies have proposed either a 2-step tunneling or a fully-coherent transport mechanism, while theoretical studies have ruled out the possibility of fully-coherent transport and suggested the need to consider other types of transport. Theoretical investigation such as DFT calculation has been used to shed light on the interactions between the charge transport properties and the internal structural changes in protein molecules.…”
Section: Deepening the Understanding Of The Electron Transport Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…26 For instance, regarding the electron transport mechanism through azurin-based junctions, there is still a debate over the mechanism of electron transport through azurin-based junctions, including the types of transport mechanism (coherent vs. incoherent) and the role of the metal ion that takes place in the system. 23,121 Experimental studies have proposed either a 2-step tunneling or a fully-coherent transport mechanism, while theoretical studies have ruled out the possibility of fully-coherent transport and suggested the need to consider other types of transport. Theoretical investigation such as DFT calculation has been used to shed light on the interactions between the charge transport properties and the internal structural changes in protein molecules.…”
Section: Deepening the Understanding Of The Electron Transport Mechanismmentioning
confidence: 99%
“…21,22 On a more fundamental level, previous studies have demonstrated that the electronic charge transport through a peptide matrix is essential for proteins to perform their functions in many biological processes such as respiration, photosynthesis, enzymatic processes, and cellular signaling, although the exact mechanism is still under debate. 16,[23][24][25][26] This has led to a myriad of theoretical and experimental studies of the electronic properties of individual protein molecules and their assimilation as active components in electronic circuits, sparking interest in the past decades and giving rise to a new field of protein-based bioelectronics, also referred to as ''proteotronics''. 3,[15][16][17][18][19]26,27 In general, protein-based bioelectronic devices rely on capturing single proteins or their monolayer onto different configurations of electrodes and exploring the electronic conductivity by measuring the current response of devices as a function of bias voltage.…”
Section: Introductionmentioning
confidence: 99%
“…These first reported studies of Az as a primary single-molecule metalloprotein probe have, however, still left challenges, taken up by other groups. 60 Open questions are, for example:…”
Section: Molecular Scale Electrochemistrymentioning
confidence: 99%
“…• High current densities have inspired rationales associated with: (i) “Coherent single-step” vs. “incoherent two-step” ET as above; 60 (ii) molecular probe orientation as for cyt b 562 , Fig. 16; 4,45 (iii) protein conformational dynamics and ET “gating”, for example as for the two-centre metalloproteins, cyt c 4 and copper nitrite reductase.…”
Section: Molecular Scale Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation